Development of a Web Based Inventory Information System - S Pasaribu, Johni (Malikussaleh University, Aceh, Indonesia, 2021)
CV. T. Kardin Pisau Indonesia is a company engaged in the manufacture of knives, having its address at Jl. Hegarmanah No.46 Bandung. As a manufacturing company, CV. T. Kardin Pisau Indonesia needs to take advantage of information technology in warehouse inventory management, no longer in manual management, namely recording in paper media, which will be vulnerable to data mismatches. Web application here is defined as an inventory application, through displays which include items to be stored in the warehouse and incoming and outgoing product transactions. The research method used here is Research and Development (RD). Making software is done with a waterfall model which consists of stages: needs analysis, design, implementation, and testing. In object orientation paradigm modeling system with visual UML. The results of this study produce web-based software using the YII Framework with the MVC (Model View Controller) method. Through a web application that provides direct contact, it is hoped that the service process to consumers can be clear and fast. This inventory application can be used as material for product inventory in warehouse stock which includes recording, processing, and reporting data on warehouse inventory. Another benefit is that with this web-based application, the head office can know the inventory in the warehouse by itself so that it can quickly take action to fill the warehouse inventory.